Enterotoxins, Biofilm and Resistance to Antimicrobial Agents of Coagulase-Negative Staphylococcus Strains Isolated from Blood Cultures - Karelis Lilibeth Nava Terán; Dalialba María Sánchez Galvis; Gladis Colina López; Kutchynskaya Valero Leal (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
Coagulase-negative staphylococci (CNS) have been identified as the etiological agent in various infections and are currently the microorganisms most frequently isolated in blood cultures. However, little is known about the virulence factors produced by CNS that contribute to the pathogenesis of infections caused by these microorganisms. This study was designed to determine the production of staphylococcal enterotoxins, biofilm production and resistance to antimicrobial agents. For this purpose, a total of 48 CNS strains isolated from blood cultures at the University Hospital in Maracaibo, Zulia, Venezuela, were studied. Staphylococcal enterotoxins were detected by reversed passive latex agglutination. Biofilm production was assessed in a quantitative assay using a microtiter-plate. Susceptibility against antimicrobial agents was tested by the disk diffusion method. Six strains of staphylococci isolates (12.5%) were found to be enterotoxigenic. Of these, 3 strains were positive for staphylococcal enterotoxin D (SED), 2 for SEA and 1 of the isolates was positive for SEB, SEC and SED.Twenty-one isolates (44%) were found to be biofilm producers. A high frequency of resistance was observed with oxacillin (90%), gentamicin (83%) and erythromycin (67%). None of the isolates showed resistance to vancomycin. Taking into consideration that the etiological importance of CNS has often been neglected, the present investigation confirmed that these microorganisms should not be ignored or classified as mere contaminants.